THU0496 [18F] Fdg Uptake in Proximal Muscles Assessed by Pet/Ct Reflects Both Global and Local Muscular Inflammation and Provides Useful Information in the Management of Patients with Polymyositis/Dermatomyositis. (23rd January 2014) - Tanaka, S.; Ikeda, K.; Uchiyama, K.; Iwamoto, T.; Sanayama, Y.; Okubo, A.; Nakagomi, D.; Takahashi, K.; Yokota, M.; Suto, A.; Suzuki, K.; Nakajima, H.
Abstract : Background: Although the utility of [ 18 F] fluoro-deoxy-glucose-positron emission tomography/computed tomography ([ 18 F] FDG-PET/CT) in the management of rheumatic or inflammatory diseases has been increasingly reported, its applications and benefits in the management of polymyositis (PM)/dermatomyositis (DM) are still controversial [1, 2 ]. Objectives: This study aimed to determine whether [ 18 F] FDG-PET/CT discriminates PM/DM from non-muscular diseases and also whether the FDG uptake in proximal muscles reflects the activity and severity of muscular inflammation in PM/DM. Methods: Twenty treatment-naïve PM/DM patients who underwent [ 18 F] FDG-PET/CT were retrospectively identified by reviewing medical records. The same number of age- and sex-matched control patients with non-muscular diseases were also identified. Standardized uptake value (SUV) was calculated for each of the seven proximal muscles. For patient-based assessment, mean proximal muscle SUV was calculated by averaging the SUVs for these proximal muscles bilaterally. Results: Mean proximal muscle SUVs were significantly greater in PM/DM patients than those in control patients (median 1.05 vs. 0.69, P < 0.001). Mean proximal muscle SUVs significantly correlated with mean proximal manual muscle test scores (rho = -0.48, P = 0.028) and serum levels of creatine kinase (rho = 0.54, P = 0.015) and aldolase (rho = 0.64, P = 0.002). Furthermore, SUVs in proximal muscles from which biopsy specimens were obtained significantly correlated with the histological grades for inflammatory cell infiltration (rho = 0.66, P = 0.002). Conclusions: Our results suggest that [ 18 F] FDG-PET/CT is useful in the diagnosis of PM/DM when inflammation in proximal muscles is globally assessed with quantitative measures. Our results also indicate that the local FDG uptake in a proximal muscle reflects the activity of inflammation in the same muscle and provides useful information in determining the region for muscle biopsy. References: Pipitone N, Versari A, Zuccoli G, et al. 18F-Fluorodeoxyglucose positron emission tomography for the assessment of myositis: a case series. Clin Exp Rheumatol 2012;30:570-3. Owada T, Maezawa R, Kurasawa K, Okada H, Arai S, Fukuda T. Detection of inflammatory lesions by f-18 fluorodeoxyglucose positron emission tomography in patients with polymyositis and dermatomyositis. J Rheumatol 2012;39:1659-65. Disclosure of Interest: None Declared